THE ROLE OF ARTISTIC LITERATURE IN THE DEVELOPMENT OF THE CHILD'S MIND - Kazakova Sayyora (Scholar Express Journals, 2023)
In this article, children's literature is an art of words and a means of education in terms of content, any work written for children is suitable for their young characteristics and levels, it is rich in vivid images that arouse thoughts in the hearts of young readers. It is mentioned that it is necessary to be an inspiration for stories, great and brilliant works, and how important the role of fiction is in the development of a child's mind.
Keywords: fairy tale; short story; stories